Lotka's Law and the Literature of Library and Information Science in Turkey Lotka Yasası ve Türkiye'de Kütüphane ve Bilgi Bilimi Literatürü - Murat Yılmaz (Türk Kütüphaneciliği, 2002)
The aim of the study is to test the applicability of Lotka's Law for the literature of library and information science in Turkey. The database of the study is 1399 papers published in The Bibliography of Articles in Turkish Periodicals between 1952 and 2000, by 604 researchers in the field of library and information science. The results of the study present the distribution of productivity of Lotka's inverse square law does not fit the distribution of the data constituted by the researchers in the field of library and information science in Turkey. In other words it was determined that Lotka's inverse square law does not apply the literature of library and information science in Turkey. Furthermore it was determined that Lotka's inverse power law fits the value of n (2,1128) calculated for the literature of library and information science in Turkey. Bu incelemenin amacı, Lotka yasasının Türkiye'deki kütüphane ve bilgi bilimi literatürüne uygulanabilirliğini test etmektir. Bu araştırmanın veri tabanı, 1952-2000 yıllan arasında Türkiye Makaleler Bibliyografyası'nda yer alan kütüphane ve bilgi bilimine ait 604 yazarın yazdığı toplam 1,399 yazıdan oluşmaktadır. Araştırmada Lotka yasasının analizi için Pao'nun prosedürü uygulanmıştır. İnceleme sonucunda Lotka'nın ters kare yasasına ait verimlilik dağılımının, Türkiye'deki kütüphane ve bilgi bilimi literatüründeki yazar topluluğunun oluşturduğu verilere ilişkin dağılıma uymadığı, diğer bir deyişle Lotka'nın ters kare yasasının, Türkiye'deki kütüphane ve bilgi bilimi literatürüne uygulanamayacağı tespit edilmiştir. Aynca Türkiye'deki kütüphane ve bilgi bilimi literatürü için tespit edilen n değerinin (2,1128) Lotka'nın ters kuvvet yasasına uyduğu saptanmıştır.